PERSPECTIVE OF THE WORD “GOBLOK” UTTERED BY UNSCRUPULOUSPREACHERS IN TERMS OF PRAGMATICS: A FORENSIC LINGUISTIC STUDY - J. Anhar Rabi Hamsah Tis’ah (PT. Anagata Sembagi Education, 2024)
This study analyzes the utterance